1999
DOI: 10.1177/104225879902300304
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Entrepreneurship and the Pursuit of Competitive Advantage

Abstract: This paper presents a theoretical exploration of the construct of corporate entrepreneurship. Of the various dimensions of firm-level entrepreneurial orientation identified in the literature, it is argued that innovation, broadly defined, is the single common theme underlying all forms of corporate entrepreneurship. However, the presence of innovation per se is insufficient to label a firm entrepreneurial. Rather, it is suggested that this label be reserved for firms that use innovation as a mechanism to redef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
755
1
33

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 959 publications
(850 citation statements)
references
References 32 publications
11
755
1
33
Order By: Relevance
“…The corporate entrepreneurship literature has also found that innovation outcomes are associated with growth (Burgelman, 1984), higher profitability (Zahra & Covin, 1995), and competitive advantage (Covin & Miles, 1999). (We note this latter point to reinforce our earlier point that while innovation and corporate entrepreneurship cover much of the same ground, one makes little reference to the other and vice versa [for an exception, see Morris, Kuratko, & Covin, 2010].…”
supporting
confidence: 52%
“…The corporate entrepreneurship literature has also found that innovation outcomes are associated with growth (Burgelman, 1984), higher profitability (Zahra & Covin, 1995), and competitive advantage (Covin & Miles, 1999). (We note this latter point to reinforce our earlier point that while innovation and corporate entrepreneurship cover much of the same ground, one makes little reference to the other and vice versa [for an exception, see Morris, Kuratko, & Covin, 2010].…”
supporting
confidence: 52%
“…The effect of pro-entrepreneurship architecture on organisational outcomes corporate intrapreneurship (Dess et al 2003), strategic entrepreneurial posture (Covin, Slevin 1989), and internal corporate venturing (Hornsby et al 2002); these not being merely differences in nomenclature, but each having specific meaning and focus. CE which includes strategic renewal (organizational renewal involving major strategic and / or structural changes), innovation (the introduction of something new to the marketplace), and corporate venturing (corporate entrepreneurial efforts that lead to the creation of new companies within the corporate company), are all important and legitimate parts of the CE process (refer to Covin, Miles 1999;Kuratko, Welsch 2001;Morris, Kuratko 2002). Sharma and Chrisman (1999) and Geisler (1993) view CE as the process whereby an individual or group of individuals, in association with an existing company, create a new company or instigate renewal or innovation within that company, or in a family business (Kellermanns, Eddleston 2006).…”
Section: Corporate Entrepreneurshipmentioning
confidence: 99%
“…I focus on incumbent firms exposed to radical technological change and analyze how they have used interfirm cooperation with new entrants as a strategy not only to adapt but also to innovate successfully. In particular, I attempt to show how corporate entrepreneurship (Zahra, 1993;Covin and Miles, 1999) pursued by large pharmaceutical firms has led to the successful adaptation to a radical innovation-in this case, the emergence of biotechnology as the new framework of drug discovery and development.…”
mentioning
confidence: 99%